2004
DOI: 10.1039/b400514g
|View full text |Cite
|
Sign up to set email alerts
|

Levels of synthetic musk compounds in municipal wastewater for potential estimation of biota exposure in receiving waters

Abstract: We analyzed water samples from the confluence of three municipal sewage treatment effluent streams, surface water, and whole carp (Cyprinus carpio) for synthetic musks for a period of 7-12 months. The lipid content of each fish was determined and compared with the concentration of musks in the whole fish tissue. Enhanced methods were used for water sampling and musk extraction. The data presented here provide insight as to the relationship between concentrations of synthetic musks in the municipal effluent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Peck and Hornbuckle (2004) report average concentrations of HHCB and AHTN in Lake Michigan at 4.7 and 1.0 ng/L, respectively, and concentrations in Lake Mead average 0.4 ng HHCB/L and 0.2 ng AHTN/L (Osemwengie and Gerstenberger 2004). In a recent survey of wastewater contaminants in streams upstream and downstream of selected towns in Iowa, concentrations of synthetic musks varied with flow conditions and ranged from 500 to 1200 ng AHTN/L and 56 to 260 ng HHCB/ L (Kolpin et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Peck and Hornbuckle (2004) report average concentrations of HHCB and AHTN in Lake Michigan at 4.7 and 1.0 ng/L, respectively, and concentrations in Lake Mead average 0.4 ng HHCB/L and 0.2 ng AHTN/L (Osemwengie and Gerstenberger 2004). In a recent survey of wastewater contaminants in streams upstream and downstream of selected towns in Iowa, concentrations of synthetic musks varied with flow conditions and ranged from 500 to 1200 ng AHTN/L and 56 to 260 ng HHCB/ L (Kolpin et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining polycyclic musk in aqueous portion is discharged with wastewater treatment plant effluent, which is being used increasingly to irrigate crops and public areas in arid regions (Pedersen et al 2005). Furthermore, some studies found that rainwater also could leach polycyclic musk compounds into surface soil (Fromme et al 2001;Osemwengie and Gerstenberger 2004). Since polycyclic musk compounds are absorbed easily and bound firmly by soil particles (clays, minerals and organic matter) (Böhm and Düring 2010;Balk and Ford 1999a), it may persistently remain in soil environment due to their high sorption, low degradability and low leaching behaviors, subsequently they can be taken up by plants or animals and accumulate in the terrestrial food chain (Böhmer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic musks are chemical products used for the manufacture of fragrances, soap scents, home cleaning products, detergents, fabric softeners, shampoo, shaving lotions and even herbicides (Nair et al, 1986;Gatermann et al, 1995) with a high consumption in the whole world (Osemwengie and Gerstenberger, 2004). They have been found present in the environment because of their high degree of use and liberation, (Rimkus et al, 1994).…”
Section: Introductionmentioning
confidence: 99%